Seven reasons that justify a democratic consultation on the FTA - Acosta, Alberto (2016)
Given that the Free trade agreement encompasses more than trade-related issues, this article poses the need of fostering a wide, participatory debate which could lead to a popular consultation. Considering the eventual consequences of the free trade agreement for the Andean countries, the author pro-poses that the whole society must decide whether the US-Andean Free Trade Agreement should or should not be signed.